WORKSHOP KARYA ILMIAH DENGAN PENGUATAN REFERENSI DAN BIBLIOMETRIK PADA SISWA MTS AL-MU’MIN MUHAMMADIYAH TEMBARAK - Savitri, Annisa Aulia; Prasetyo, Ridho; Faturachman, Gavriel Fauzan; Khusna, Sausan Salsabila; Dewantara, Aditya Arya; Claus, Matheus Prayoga; Fauziah, Rizza; Yanuarti, Nurhaliza; Putri, Izzati Amelia; Fawwaz, Naufal Erlang; Prianita, Devi Rambu (Universitas Mataram, 2025)
This community service program was carried out in May 2025, involving 62 students from grades X, XI, and XII. The activity was initiated in response to the low level of scientific literacy among students at MTs Al-Mu’min Muhammadiyah Tembarak, particularly in the areas of data analysis, scientific writing structure, and the use of credible reference sources. The problems addressed in this program include improving students’ conceptual understanding of scientific writing and strengthening their practical skills in producing academic work that adheres to scientific standards. The purpose of the activity was to equip students with essential knowledge, technical writing skills, and the ability to utilize supporting technologies through systematic training and direct mentoring. The methods employed consisted of initial observation, interactive workshop sessions, two-way discussions, practical tasks in developing outlines and abstracts, and evaluation using questionnaires and Likert-scale surveys. The results indicated a meaningful improvement in students’ understanding, reflected by achievement levels of 100% for basic scientific writing concepts, 91.9% for reference and writing conventions, 87.1% for technology utilization, and 74.2% for writing structure. The activity evaluation also showed predominantly positive responses in the agree to strongly agree categories, ranging from 38.7% to 66.1%. These findings demonstrate that the implemented training approach effectively enhanced both the conceptual and practical abilities of the students. In conclusion, the program successfully improved students’ scientific literacy and writing skills. Suggestions for future activities include providing continued mentoring, optimizing the use of writing-support technologies, and integrating project-based learning to ensure sustained mastery of scientific skills.